AB0194 VITAMIN D TRAJECTORIES IN EARLY DIAGNOSED, AGGRESSIVELY TREATED RHEUMATOID ARTHRITIS PATIENTS: A 10 YEAR LONGITUDINAL COHORT STUDY BASED ON THE DANISH CIMESTRA TRIAL. (2nd June 2020) - Herly, M.; Stengaard-Pedersen, K.; Vestergaard, P.; Christensen, R.; Möller, S.; Ǿstergaard, M.; Junker, P.; Hetland, M. L.; Hørslev-Petersen, K.; Ellingsen, T.
Abstract : Background: Low vitamin D levels are common in Rheumatoid Arthritis (RA) 1, and possibly associated with disease course, 2 but data on vitamin D levels during long-term disease course has not been reported previously. Objectives: To describe vitamin D trajectories from time of diagnosis through 10 years follow-up in early diagnosed RA patients. Methods: The CIMESTRA trial included 160 newly diagnosed RA-patients, treated aiming at remission with methotrexate and intraarticular steroid, further randomized to ciclosporine or placebo. Vitamin D supplementation was recommended according to national guidelines. Vitamin Dtotal was measured at diagnosis, and year 1, 5 and 10 using LC-MS/MS. 1, 25(OH)2 D was measured at diagnosis and year 1 using RIA. Linear mixed effects models were used to study vitamin D levels serially. We had fixed effects for time, and patients modelled as a random effect. We tested the hypothesis that percentage of patients achieving Dtotal ≥ 50 nmol/l during follow-up was 90%. Analyses of associations between Dtotal and DAS28-CRP during the disease-course were adjusted for age, sex, symptom-duration prior to diagnosis and season of diagnosis. Results: Median Dtotal at baseline was 53 nmol/l (IQR 36-567.8). Dtotal increased significantly during follow-up, independently of level at diagnosis (p<0.001). Individuals achieving Dtotal ≥50nmol/l during follow-up was 80-87%, but not as high as 90% at year 1 and 5, p<0.002. DAS28-CRP during disease-course was inversely associated with Dtotal trajectories only in crude (β-coefficient (β) -0.0034, 95%CI (-0.007; -0.0002) p=0.039) and partially adjusted analyses (β -0.003, 95%CI (-0.007; -0.002) p=0.04). Estimate was left insignificant in fully adjusted analyses (β -0.003, 95%CI (-0.0006; 0.0001) p=0.06). 1, 25(OH)2 D levels did not change significantly during follow-up (p=1.00). Conclusion: Dtotal increased significantly during follow-up, but fewer than 90% achieved the recommended 50 nmol/l at year 1 and 5. Disease activity during follow-up was associated with Dtotal trajectories only in partially adjusted analyses, while adjustment for possible confounders left estimates insignificant. Results suggest vitamin D supplementation to be recommended in all RA patients. References: Reference List [1]Herly M, Stengaard-Pedersen K, Vestergaard P, et al. The D-vitamin metabolite 1, 25(OH)2 D in serum is associated with disease activity and Anti-Citrullinated Protein Antibodies in active and treatment naive, early Rheumatoid Arthritis Patients. Scand J Immunol 2018;88(3):e12704. doi: 10.1111/sji.12704 [2]Mouterde G, Gamon E, Rincheval N, et al. Association between Vitamin D deficiency and disease activity, disability and radiographic progression in early rheumatoid arthritis. The ESPOIR cohort. J Rheumatol 2019 doi: 10.3899/jrheum.190795 Disclosure of Interests: Mette Herly Grant/research support from: Pfizer Denmark - "Unrestricted Grant" for PhD project Danish Rheumatism Association, Research Grant, Speakers bureau: Speaker for Danish Rheumatism Association, Kristian Stengaard-Pedersen: None declared, Peter Vestergaard: None declared, Robin Christensen: None declared, Sören Möller: None declared, Mikkel Ǿstergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Merck, and Novartis, Consultant of: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Peter Junker: None declared, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen and Pfizer, Consultant of: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck and Samsung Bioepis, Kim Hørslev-Petersen Grant/research support from: Pfizer (Travel expences), Torkell Ellingsen: None declared